THE EFFECT OF DIGITAL LITERACY AND FAMILY SUPPORT ON THE ENTREPRENEURIAL INTEREST OF GRADE XII OFFICE MANAGEMENT STUDENTS AT SMKN 1 SURABAYA - Ardianto, Ferdi; Maula, Farij Ibadil (Perspektif Ilmu Pendidikan, 2026)
The present investigation sought to examine the impact of digital literacy and familial support on the entrepreneurial proclivity of 12th-grade Office Management students at SMK Negeri 1 Surabaya during the 2024/2025 academic year. Entrepreneurial interest is considered a crucial determinant in equipping students to navigate prospective career challenges, particularly within the digital epoch, which necessitates technological competence and environmental reinforcement. This study employed a quantitative methodology with a causal-associative research design. The population consisted of 138 students, from which a sample of 103 students was drawn utilizing stratified random sampling. Data acquisition was conducted through a questionnaire and subsequently analyzed via multiple linear regression. The findings revealed that digital literacy and familial support exhibit a statistically significant and affirmative influence on students’ entrepreneurial interest, observable in both isolated and combined analyses. Digital literacy empowers students to proficiently leverage technology for identifying and cultivating business opportunities, while familial support fortifies motivation and self-assurance in pursuing entrepreneurial endeavors. A coefficient of determination (R² = 0.414) revealed that these two variables elucidated 41.4% of the variance in entrepreneurial interest, with unexamined factors accounting for the residual proportion. These insights underscore the criticality of reinforcing digital literacy and familial encouragement for nurturing students’ entrepreneurial drive, thereby offering practical ramifications for educational institutions and households in formulating pedagogical strategies supportive of entrepreneurial development.